Pelatihan Penelitian Tindakan Kelas untuk Meningkatkan Produktivitas Guru - Isna Rezkia Lukman; Herizal Herizal; Agus Muliaman; Syafrizal Syafrizal (STKIP Andi Matappa, 2021)
The Community Service Program (PKM) aimed to improve teachers’ understanding about how to write a scientific article through classroom action research. The program which was training about classroom action research was held for 42 teachers of MTsS and MAS Syamsuddhuha, North Aceh. The training was held face to face with health protocols. The topics were introduction of classroom action research, classroom action research with e-learning, statistics in classroom action research, anbuso program, and academic writing technique. During the training, the teachers were enthusiastic. It could be seen on a session, they asked many questions and told more about their experiences. The result of the program showed that the teachers could understand about classroom action research procedures. In academic writing session, they could identify the components that must be present in the introduction, methods, and results and discussion of the example article given. It can be concluded that the training has positive impact on the teachers.